Pharmacists' immunization experiences, beliefs, and attitudes in New Brunswick, Canada - Isenor JE; Slayter KL; Halperin DM; McNeil SA; Bowles SK (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Background: The expansion of pharmacist scope of practice to include provision of immunizations has occurred or is being considered in various countries. There are limited data evaluating the experiences of Canadian pharmacists in their role as immunizers. Objective: To describe the experiences of pharmacists in the Canadian province of New Brunswick as immunizers, including vaccines administered and perceived barriers and facilitators to providing immunizations. Methods: An anonymous, self-administered, web-based questionnaire was offered via email by the New Brunswick Pharmacists' Association to all its members. The survey tool was adapted, with permission, from a tool previously used by the American Pharmacists Association and validated using content validity and test-retest reproducibility. Pharmacist reported immunization activities and perceived facilitators and barriers to providing immunization services were assessed. Results: Responses from 168 (response rate of 26%) were evaluable. Approximately 90% of respondents worked in community practice full time, 65% were female and 44% were practicing for 20 or more years. Greater than 75% reported administering: hepatitis A and B, influenza, and zoster vaccines. The majority of respondents felt fully accepted (agreed or strongly agreed) as immunization providers by patients, local physicians, and the provincial health department (97%, 70%, and 78%, respectively). Most commonly reported barriers were: lack of a universally funded influenza immunization program, insufficient staffing and space, and concerns around reimbursement for services. Conclusions: Pharmacists in New Brunswick, Canada are actively participating in the provision of a variety of immunizations and felt fully supported by patients and other healthcare providers. Barriers identified may provide insight to other jurisdictions considering expanding the role of pharmacists as immunizers.